Akuntansi Mudharabah sebagai Instrumen Transparansi Keuangan Syariah - Malinda, Sri; Umasugi, Nirwan (Peneliti.net, 2026)
Transparency is a fundamental principle in Islamic financial institutions as it reflects accountability, trust, and compliance with Sharia values. Mudharabah, as a profit-sharing contract based on trust between capital owners and fund managers, requires transparent financial reporting to avoid information asymmetry and moral hazard. This study aims to examine the role of mudharabah accounting as an instrument for enhancing financial transparency in Islamic finance. The research employs a qualitative descriptive approach using library research methods. Data were collected from PSAK 105 on Mudharabah Accounting, accredited national journals, and relevant Islamic accounting literature. Data analysis was conducted through content analysis to examine the conformity between mudharabah accounting practices and the principles of transparency in Islamic finance. The findings indicate that mudharabah accounting, when implemented in accordance with PSAK 105, significantly supports transparency by ensuring proper recognition, measurement, presentation, and disclosure of financial information. Moreover, transparent mudharabah accounting contributes to increased accountability and public trust in Islamic financial institutions.